Micronutrients Associated With Anemia in School-age Children and Adolescents 2005–2018: Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) Project - Rochelle Werner; Hanqi Luo; Lei Liu; Yuqing Wang; Jiaxi Geng; Yi-An Ko; Parminder S Suchdev; Yaw Addo; Zulfiqar Ahmed Bhutta; Victor Temple; Frank Wieringa; Fabian Rohner; et al. (Current Developments in Nutrition)
Background: School-age children and adolescents may be at risk of anemia through demands on micronutrients required for growth and maturation. Objectives: This multicountry analysis examined the burden of anemia in children aged 5–19 y by sex and age category and associations with micronutrient deficiencies, inflammation, and BMI. Methods: Children aged 5–19 y from surveys in the Biomarkers Reflecting Inflammation and Nutritional Determinants of Anemia (BRINDA) Project were included with hemoglobin, ≥1 micronutrient (iron, vitamin A, folate, vitamin B12, or zinc) and inflammation biomarker, and n > 100 per survey. Factors with bivariate relationships with anemia (P < 0.1) were included in multivariable modified Poisson regression models to examine the attributable burden of anemia. Results: This analysis included 54,534 children from 17 surveys in 16 countries (16 surveys for 15–19 y; 9 surveys for 10–14 y; 8 surveys for 5–9 y). Median overall anemia prevalence was 16% (range: 5% in Ecuador, United Kingdom, and United States to 59% in Côte d’Ivoire) with the highest burden in 15–19-y-old females (24%). In most surveys, anemia prevalence did not differ by sex for children aged 5–14 y, and median anemia prevalence was lower in children aged 10–14 y (7%) than in those aged 5–9 y (9%) or 15–19 y (22%). In most surveys, higher anemia prevalence was associated (P < 0.05) with iron deficiency (15%) [prevalence ratio (PR): 1.6–14.2; 5–9 y, 4/7 surveys; 10–14 y, 6/6 surveys; 15–19 y, 13/14 surveys), vitamin A deficiency (2%) (PR: 1.8–3.0; 5–9 y, 2/2 surveys; 10–14 y, 2/3 surveys; 15–19 y, 2/3 surveys), and inflammation (13%) (PR: 1.4–2.4: 5–9 y, 4/4 surveys; 10–14 y, 2/4 surveys; 15–19 y, 6/8 surveys). Folate, vitamin B12, zinc, and BMI had weak, variable associations with anemia. Conclusions: Iron deficiency and vitamin A deficiency are consistently associated with anemia in school-age children and adolescents, whereas inflammation and other micronutrients had context-dependent associations. This research underscores the importance of examining multiple micronutrients associated with anemia in the context of factors such as country, age, and sex.